Exploration of the Driving Path of Digital and Intelligent Transformation of Automobile Manufacturing Enterprises: Based on the Dynamic QCA Analysis - Luo, Ling; Tang, Yuan; Wei, Suting (International Journal of Global Economics and Management, 2025)
The digital economy is a major trend in the global economic development,in such an economic wave,intelligent manufacturing has become a new highland of competition.It has become the trend of The Times to take intelligent manufacturing as the main development direction and promote the upgrading of manufacturing industry to digitalization and intelligence.Based on the TOE analysis framework, this paper takes 27 automobile manufacturing enterprises from 2018 to 2022 as the research object, uses R-Studio software to carry out dynamic QCA analysis, and explores the path of mathematical transformation of automobile manufacturing enterprises driven by the antecedent conditions of ' technology-organization-environment ' dimension from the perspective of configuration. The research shows that any single antecedent condition cannot independently become a necessary condition to drive the digital intelligence transformation of automobile manufacturing enterprises.The level of digital intelligence transformation of high-level enterprises is affected by the ' multiple concurrency ' of six conditions : intelligent production, technology R & D capability, knowledge talent investment, management transformation planning, government support and digital innovation environment, and has formed three types of configuration modes : digital technology + R & D environment-driven, digital technology + organizational planning-driven and digital technology + high-end talent-driven.The technological R & D capability in the technical dimension and the digital innovation environment in the environmental dimension are the core reasons for the failure of the digital intelligence transformation of the automobile manufacturing industry. Based on the research conclusions, this paper puts forward relevant policy suggestions to promote automobile manufacturing enterprises to accelerate the transformation of digital intelligence from the aspects of strengthening the application of configuration coordination thinking, grasping the investment in technology research and development, and the government 's assistance in digital environment optimization.